1992
DOI: 10.1007/bf00619758
|View full text |Cite
|
Sign up to set email alerts
|

Emission spectra and cross-section spectra of neodymium laser glasses

Abstract: Amplified spontaneous emission spectra and light amplification spectra of some

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…From the F-L equation, it can be seen that the σ em value is directly proportional to the fourth power of λ p and is inversely proportional to the ∆λ eff . It has been observed that the redshift in λ p always causes an increase in ∆λ eff in the 1.06 µm emission of Nd, hence restricting the larger σ em value to attain [47]. Therefore, it is important to optimize the λ p and ∆λ eff values to maximize the emission cross section of a particular host.…”
Section: Discussionmentioning
confidence: 99%
“…From the F-L equation, it can be seen that the σ em value is directly proportional to the fourth power of λ p and is inversely proportional to the ∆λ eff . It has been observed that the redshift in λ p always causes an increase in ∆λ eff in the 1.06 µm emission of Nd, hence restricting the larger σ em value to attain [47]. Therefore, it is important to optimize the λ p and ∆λ eff values to maximize the emission cross section of a particular host.…”
Section: Discussionmentioning
confidence: 99%
“…A large value of stimulated emission cross-section is a desired property for low threshold, high gain applications and high efficient laser. sEmission peak wavelengths (λ p ), effective bandwidths (Δυ eff ), peak stimulated emission cross-sections (σ p ), optical gain parameters (σ p × τ R ) and optical gain bandwidths (σ p × Δν eff ) of 1 mol% Nd 3+ doped lithium tetraborate glass matrices have been calculated using the standard equations and are tabulated in table 8 [45]. From the table is observed that among the four glass matrices (Li, Ba, Ca, Na) studied, LiBiNaTNd glass matrix shows higher emission cross section, while comparing of mixed modifiers, LiBiLiNaTNd shows higher emission cross section.…”
Section: Analysis Of Emission Spectramentioning
confidence: 99%
“…Specification of the model parameters and for the studied R6G- and DCM-based systems was carried out using the results of preliminary experiments and datasets reported in the literature (see Table 2 ). In particular, a cross section of the stimulated emission can be obtained using the following expression [ 46 , 47 ] with further spectral averaging Here, is the characteristic time of the fluorescence decay. Figure 6 displays the recovered values of for the examined R6G- and DCM-based systems against the pump intensity.…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…Specification of the model parameters σ a , δ, hν f λ , and σ st λ for the studied R6Gand DCM-based systems was carried out using the results of preliminary experiments and datasets reported in the literature (see Table 2). In particular, a cross section of the stimulated emission can be obtained using the following expression [46,47]…”
Section: Modeling Of the Extreme Saturated States In Laser-pumped Flu...mentioning
confidence: 99%